2023
DOI: 10.1371/journal.pone.0281180
|View full text |Cite
|
Sign up to set email alerts
|

Variation of sensitivity of Trypanosoma evansi isolates from Isiolo and Marsabit counties of Kenya to locally available trypanocidal drugs

Abstract: Trypanocidal resistance is a major cause of treatment failure. This study evaluated the sensitivity of Trypanosoma evansi field isolates collected from Marsabit and Isiolo counties, Kenya. A total of 2,750 camels were screened using parasitological tests for trypanosomes. Of the screened camels, 113 tested positive from which 40 T. evansi isolates were tested using the single dose mice sensitivity test. Five treatment groups each comprising of 6 mice were inoculated intraperitoneally with 1x105 trypanosomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(94 reference statements)
2
4
0
Order By: Relevance
“…Herd prevalence variations were observed in the present study with the highest herd prevalence recorded in Loglogo (inhabited by the majority Rendille ethnic community) at the beginning of the dry season, followed by Kula Mawe (inhabited by the majority Borana ethnic community) during the rainy season, and finally Turbi (inhabited by the majority Gabbra ethnic community) at the peak of the dry season, which may be attributed to different Surra management practices by the communities as previously established [34]. Previous studies conducted in different localities in Somaliland and Ethiopia, both located in the Horn of Africa camel-keeping belt, reported comparable geographic [2,26] and herd [22] variations in trypanosomiasis prevalence.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Herd prevalence variations were observed in the present study with the highest herd prevalence recorded in Loglogo (inhabited by the majority Rendille ethnic community) at the beginning of the dry season, followed by Kula Mawe (inhabited by the majority Borana ethnic community) during the rainy season, and finally Turbi (inhabited by the majority Gabbra ethnic community) at the peak of the dry season, which may be attributed to different Surra management practices by the communities as previously established [34]. Previous studies conducted in different localities in Somaliland and Ethiopia, both located in the Horn of Africa camel-keeping belt, reported comparable geographic [2,26] and herd [22] variations in trypanosomiasis prevalence.…”
Section: Discussionsupporting
confidence: 52%
“…This may be an indication that either the LMD area and/or the grazing areas of LMD camel keepers may not have biting flies or circulating trypanosome isolates or may point to better management practices and grazing patterns by the Somali ethnic community residing in the region. Indeed, our earlier survey on knowledge and trypanocidal use by the ethnic communities in the study area revealed that the Somali ethnic group residing in the LMD area were the most knowledgeable on camel Surra and recorded the highest prophylactic use of quinapyramine sulphate and chloride [34]. Nonetheless, the vector survey captured a few biting flies known to transmit trypanosome infection in the LMD region, although an assessment of fly infectivity was not carried out.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The disease impacts impoverished livestock farmers and threatens food security and livelihoods. There are no effective vaccines against the trypanosome parasites [ 7 ] and most field trypanosome isolates have developed resistance against available antitrypanosomal drugs [ 8 , 9 ]. Prospects of using trypanotolerant cattle remain, but viability for wide scale adoption is not clear [ 10 ].…”
Section: Introductionmentioning
confidence: 99%